CARBON CREDIT DAN FAKTOR-FAKTOR LAIN YANG BERPENGARUH TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - RIKI SANJAYA (Jurnal Bisnis dan Akuntansi, 2017)
The objectives of this research is to test and analyze whether growth opportunities, firm size, cash ratio, firm age, carbon credit, debt ratio and non-debt tax shield have influence to firm performance. This study was also to find something new which seldom to do with researchers in Indonesian about carbon credit and improve consistency of results from prior researchers. Sample in this research are manufacturing companies with industry classification basic industry and chemicals, which are listed from December 2010 until December 2015 in Indonesian Stock Exchange with research time period from 2010 until 2015. Only 40 companies meet the criteria and taken as samples. The samples of this research collected using purposive sampling. This research used multiple regression. The result of this research show that firm size and debt ratio influence firm performance on manufacturing companies with industry classification basic industry and chemicals listed in Indonesian Stock Exchange. On the other hand growth opportunities, cash ratio, firm age, carbon credit and non-debt tax shield not influence firm performance. While simultaneously, all the variables in this research influence firm performance.